Towards a multidisciplinary approach in creative subtitling - McClarty, Rebecca (MonTi Monografías de Traducción e Interpretación, 2014)
Standard subtitling practices have long been influenced, if not governed, by norms and conventions such as the Code of Good Subtitling Practice (Ivarsson & Carroll 1998). Yet recent research into film subtitling has begun to take a creative turn: a trend that is matched by increasing numbers of fansubs and professionally produced creative subtitles. This paper seeks to demonstrate the need for a multidisciplinary approach to creative subtitling and, by drawing upon principles from film studies, suggests some key features for the development of a creative subtitling practice.